Cancer overturned: Endometrioma mimicking granulosa cell tumor and the importance of FOXL2 analysis - Emily R. Rosen; David M. Kushner; Aparna M. Mahajan; Cara R. King (Elsevier, 2019)
Background: Various ovarian neoplasms may show histological findings that are morphologically indistinguishable from adult granulosa cell tumor (AGCT). Case presentation: A 36 year-old women presented with left lower extremity pain and numbness. Ultrasound revealed a 10 cm left adnexal mass treated with ovarian cystectomy. Histopathology revealed endometriotic cyst with intramural granulosa cell tumor. She underwent a laparoscopic left salpingo-oophorectomy and omental biopsy by Gynecologic Oncology. Pathologic review of residual ovarian abnormality prompted a molecular analysis. FOXL2 gene mutation was absent supporting the diagnosis of benign endometrioma. Conclusions: A somatic missense mutation in the FOXL2 gene is a sensitive molecular marker for AGCT. Mutation analysis can help distinguish malignant from benign pathology to provide appropriate treatment and disease surveillance.